Importance of comprehensive genetic testing for patients with suspected vascular Ehlers–Danlos syndrome: a family case report and literature review - Wei, Xianda; Zhou, Xu; Xie, BoBo; Shi, Meizhen; Gui, Chunrong; Liu, Bo; Li, Caiyan; Zhang, Chi; Luo, Jiefeng; Mi, Cundong; Gui, Baoheng (Frontiers in Genetics, 2023)
Vascular Ehlers-Danlos syndrome (vEDS), the most severe type of Ehlers-Danlos syndrome, is caused by an autosomal-dominant defect in the COL3A1 gene. In this report, we describe the clinical history, specific phenotype, and genetic diagnosis of a man who died of vEDS. The precise diagnosis of this case using whole-exome sequencing provided solid evidence for the cause of death, demonstrating the practical value of genetic counseling and analysis. Early diagnosis for the proband's son, who was also affected by vEDS, revealed initial complications of vEDS in early childhood, which have rarely been reported. We also reviewed the literature on COL3A1 missense mutations and related phenotypes. We identified an association between digestion tract events and non-glycine missense variants, which disproves a previous hypothesis regarding the genotype-phenotype correlation of vEDS. Our results demonstrate the necessity of offering comprehensive genetic testing for every patient suspected of having vEDS.